2002
DOI: 10.2113/173.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Nature and genesis of spodic horizons characterized by inverted color and organic content in a subalpine podzolic soil (Pyrenees Mountains, France)

Abstract: Podzolic soils showing an inverted sequence between Bh and Bs horizons have been recently described in the French Pyrenees. This paper deals with the spodic characters of two inverted podzol profiles found in the granitic Estibère valley. Taking into consideration a coherent genesis of these soils, we perform this study through a multidisciplinary approach (e.g., pedology, mineralogy). We describe the evolution of the different forms of free iron and aluminum in relation to organic constituents and the minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Similar trends were found by Remaury et al (2002) under P. uncinata in the French Pyrenees. The total organic carbon content (TOC) is higher in some strongly bleached E than in Bs horizons (i.e., P6); this may be due to fine roots accidentally included in the samples.…”
Section: Chemical Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…Similar trends were found by Remaury et al (2002) under P. uncinata in the French Pyrenees. The total organic carbon content (TOC) is higher in some strongly bleached E than in Bs horizons (i.e., P6); this may be due to fine roots accidentally included in the samples.…”
Section: Chemical Propertiessupporting
confidence: 83%
“…According to Remaury et al (2002), the crystalline Fe oxides (Fe dFe o ) in Bs horizons are the product of in situ weathering of Fe-bearing primary minerals. In the studied profiles, high Fe d values in the Bs horizons are related to large amounts of Fe tot , associated with much lower values in the overlying E and in the underlying C horizons; the hypothesis of the above-mentioned authors therefore does not fit the observed situation in the study area.…”
Section: Bulk Chemical Compositionmentioning
confidence: 99%
“…1A). Soils in the Estibère watershed have been the subject of previous studies (Remaury, 1999(Remaury, , 2002.…”
Section: Methodsmentioning
confidence: 99%
“…Rocky crests are covered by heath and pine whereas depressions are more or less colonized by hydromorphic vegetation. Two types of soil develop over the granitic units: ranker type soils under grassland and podzolic type soils mainly located on slopes and rocky zones more or less colonized by open forest and ericaceae (Remaury et al, 1999(Remaury et al, , 2002. Both are thin, acid, and have a high organic matter content.…”
Section: The Estibère Watershedmentioning
confidence: 99%
See 1 more Smart Citation